A social history of Christian origins: the rejected Jesus - Joseph, Simon J. (Routledge Studies in the Early Christian World Ser., 2022)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- Introduction -- Part I -- Chapter 1 The Jewish Problem -- Chapter 2 Jewish Jesus, Christian Christ -- Chapter 3 Theorizing Rejection -- Chapter 4 Criteria of Rejection -- Chapter 5 "Do This in Memory of Me" -- Part II -- Chapter 6 "He Was Despised and Rejected by Men" -- Chapter 7 The Rejection of the Law -- Chapter 8 The Rejection of Israel -- Chapter 9 The Rejection of the Collection -- Chapter 10 The Jewish Rejection of Jesus -- Conclusion -- Bibliography -- Index.